DIGITAL MARKETING ANALYSIS IN OPTIMIZING ROOM ADVERTISING SYARIAH HOTEL IN SEMARANG CITY (CASE STUDY AT GRASIA HOTEL SEMARANG (International Conference on Social and Islamic Studies, 2022)
This research focuses on digital marketing analysis in optimizing room advertising for syariah hotel in Semarang city. Digital marketing that is carried out to restore and revive the economic sector through halal tourism that has potential to increase the income of halal accommodation facilities for syariah hotels in Indonesia, especially in the Semarang city. The purpose of this study is to find out digital marketing activities that are implemented in syariah hotel, especially in Grasia Hotel Semarang, so that can optimize room advertising. This research uses descriptive qualitative with and interpretive paradigm and a case study approach that focuses on digital marketing and advertising which are online marketing activities for Grasia Hotel Semarang. The method of data collection uses by interviewing informants corresponding criteria for the objectives research, field observations by author during internship period, and documentation in photos, videos, recordings, and documents. The object of this research is Grasia Hotel Semarang and the conclusion is from data triangulation. The results of this study are digital marketing activities in accordance with marketing communication theory in optimizing room advertising for syariah hotels that already have halal certificate from the Indonesian Ulema Council at Grasia Hotel Semarang through digital marketing tools such as social media and OTA (Online Travel Agent) as well as the process of creating concepts of digital content on social media or OTA by implementing the advertising function in persuading potential guest to stay at Grasia Hotel Semarang, there are by informing, persuading, reminding, adding value, and assisting the guest as well as the impact of reviews or testimonials given by guest on OTA (Online Travel Agent) application, TripAdvisor, and Google Maps review. The existence of the application of digital marketing can have implications for syariah hotel room advertising to the optimum and increase the syariah hotel revenue.